Role of Blockchain Technology in Supply Chain Management - Al Maashari, Jaifar Ahmed (International Journal of Supply Chain Management, 2025)
Blockchain technology has drew interest for its capability in supply chain management to has prompt efficiency in terms of improved transparency. Blockchain has received a lot of attention with its promises of improving supply chain through accountability. This paper aims to evaluate the benefits and risks of incorporating blockchain in supply chain management networks with especial focus on peer-reviewed articles, conference papers, and literatures documented between 2015 to 2021. From the paper, it is apparent that blockchain brings critical advantages, such as real-time tracking of product movement, less fake products, and fewer errors, which is stored in the shared platform for every stakeholder’s view. Also, the use of smart contracts promotes automated execution of a contract so that the responsibility and performance of agreements are enhanced as well as operationalism. Combine examples of Walmart and IBM’s operation solution Food Trust and the shipping logistics platform Trade Lens to demonstrate the use of blockchain for the optimistic outcome in different fields. However, the broad implementation of blockchain has some barriers; these are; reluctance by the supply chain executor to adopt new structures and systems among partners, high initial costs, and diversity with blockchain solutions that does not support operational norms across platforms. These challenges therefore call for more concentrated efforts in enhancing the understanding of education on blockchain technology and supply chain actors, setting of standard practices for the ecosystem and associating the pertinent players to allow for the considerably more effective operation of the technology. This research is useful for those academics as well as practitioners who are planning to pursue the strategy of blockchain implementation in supply chain management. The direction for further research should be to address the mentioned challenges and identify the state-of-the-art approaches, formats and standards, and the ways of implementing them in practice.